Mechanisms for financial management and sustainability: the case of St. Joseph’s Hospital Koforidua - Ewusie, Georgina (2011)
A thesis submitted to the Department of Community Health, School of Medical Sciences, College of Health Sciences Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of MSc.degree in Health Services Planning and Management,